Radicals derived from acetaldehyde and vinyl alcohol. Issue 40 (4th September 2017) - Estep, Marissa L.; Morgan, W. James; Winkles, Alexander T.; Abbott, Adam S.; Villegas-Escobar, Nery; Mullinax, J. Wayne; Turner, Walter E.; Wang, Xiao; Turney, Justin M.; Schaefer, Henry F.
Abstract : We reassign several fundamental modes of radicals implicated in butanol combustion and report values for unobserved fundamentals and absolute energetics. Abstract : Vinyl alcohol and acetaldehyde are isoelectronic products of incomplete butanol combustion. Along with the radicals resulting from the removal of atomic hydrogen or the hydroxyl radical, these species are studied here using ab initio methods as complete as coupled cluster theory with single, double, triple, and perturbative quadruple excitations [CCSDT(Q)], with basis sets as large as cc-pV5Z. The relative energies provided herein are further refined by including corrections for relativistic effects, the frozen core approximation, and the Born–Oppenheimer approximation. The effects of anharmonic zero-point vibrational energies are also treated. The syn conformer of vinyl alcohol is predicted to be lower in energy than the anti conformer by 1.1 kcal mol −1 . The alcoholic hydrogen of syn -vinyl alcohol is found to be the easiest to remove, requiring 84.4 kcal mol −1 . Five other radicals are also carefully considered, with four conformers investigated for the 1-hydroxyvinyl radical. Beyond energetics, we have conducted an overhaul of the spectroscopic literature for these species. Our results also provide predictions for fundamental modes yet to be reported experimentally. To our knowledge, the ν 3 (3076 cm −1 ) and ν 4 (2999 cm −1 ) C–H stretches for syn -vinyl alcohol and all but one of the vibrational modes for anti -vinyl alcohol ( ν 1 – ν 14 ) are yet to be observed experimentally. For the acetyl radical, ν 6 (1035 cm −1 ), ν 11 (944 cm −1 ), ν 12 (97 cm −1 ), and accounting for our changes to the assignment of the 1419.9 cm −1 experimental mode, ν 10 (1441 cm −1 ), are yet to be observed. We have predicted these unobserved fundamentals and reassigned the experimental 1419.9 cm −1 frequency in the acetyl radical to ν 4 rather than to ν 10 . Our work also strongly supports reassignment of the ν 10 and ν 11 fundamentals of the vinoxy radical. We suggest that the bands assigned to the overtones of these fundamentals were in fact combination bands. Our findings may be useful in constructing improved combustion models of butanol and in spectroscopically characterizing these molecules further.